Imagining the University - Barnett, Ronald (International Higher Education, 2013)
Recent transformations in the relationship of knowledge to the economy and in the implementation of 'neoliberal' policies have seen, worldwide, an emergence of 'the entrepreneurial university'. Several reactions to this phenomenon can be identified, indicative of different forms of imagining the university. And yet, we can justifiably speak of a poverty of the imagination, for there are few ideas of the university that are sensitive to the deep structures of the university, suitably critical of the contemporary situation but yet duly optimistic about its possibilities. What are needed, therefore, is not more ideas of the university but better ideas. In particular, what are called for are feasible utopias of the university. One such feasible utopia is sketched here, namely that of the ecological university. The article ends with a reflection on the implications of the analysis here for university leadership.